CÔNG NGHỆ MẠ XOA VỚI NANO COMPOZIT Ni-TiO2, SiC - Dư, Đào Khánh; Kết, Nguyễn Duy; Hùng, Nguyễn Đức (Vietnam Journal of Chemistry, 2012)
The brush electroplating not only recovers defective areas of machine parts caused by abrasion but also improves the quality of plating surfaces better by using this composite plating solution with inert and rigid particles, especially the nanoparticles such as TiO2, SiC. The purpose of this article was to determine the solution compositions Ni-TiO2, Ni-SiC plating in order to enhance the efficiency and the physico-mechanical properties of plating layers. Results showed that using of solution NiCl2, NH4Cl, (NH4)3C6H5O7 with nanoparticle TiO2 (5.5 g/l), SiC (4.2 g/l) the plating rate can be increased to 100 mA/dm2 and the efficiency as well as the physico-mechanical properties of plating layers was improved.